Economic Appraisal of Regulatory Reform - Checklist of Issues - Mackie, Peter; Nellthorp, Peter; Laird, James (World Bank, Washington, DC, 2012)
The purpose of this brief note is to set out a checklist of issues which need to be considered when assessing the likely economic impact of regulatory reform. There is a great deal of relevant world literature, but a note of caution is appropriate when considering the transferability of experience, and especially outcome, from one country to another. Circumstances alter cases.